European rules of civil procedure - European Law Institute; International Institute for the Unification of Private Law (Oxford : Oxford University Press, 2021)
This volume was developed as part of a cooperative project of the European Law Institute (ELI) and the International Institute for the Unification of Private Law (UNIDROIT), dealing with civil procedure law. The long-term project began in February 2014 and ended in February 2020.
This edition also issued in print: 2021.
Specialized.
Description based on online resource; title from home page (viewed on October 6, 2021).
Keywords: Civil procedure -- Europe; Law; Laws of specific jurisdictions & specific areas of law